2009
DOI: 10.1254/jphs.09110fp
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil, a Long-Acting Inhibitor of PDE5, Improves Pulmonary Hemodynamics and Survival Rate of Monocrotaline-Induced Pulmonary Artery Hypertension in Rats

Abstract: Abstract. The aim of this study was to assess the effect of tadalafil (0.5, 2.5, and 10 mg /kg per day) on the progression of pulmonary arterial hypertension (PAH) in early treatment and on the survival rate in late treatment on the monocrotaline (MCT)-induced PAH rat model. Tadalafil was administered once daily to rats for 3 weeks from the day of MCT-injection or 21 days after the injection. With early treatment, tadalafil at 10 mg/kg per day prevented the development of PAH by maintaining mean pulmonary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 39 publications
(30 reference statements)
7
34
0
2
Order By: Relevance
“…15 Sawamura et al suggested that tadalafil is effective in the treatment of the late phase of pulmonary arterial hypertension through relaxation of pulmonary arteries in lungs. 16 In addition, the acute effect of tadalafil as a reno protective agent was demonstrated in experimental renal ischemia/reperfusion injury model in the rat. 17 More recently, Wang et al demonstrated that tadalafil is effective and safe for the treatment of diabetic neuropathy as it increases regional blood flow in the sciatic nerve tissue and improves peripheral nerve function in type II diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…15 Sawamura et al suggested that tadalafil is effective in the treatment of the late phase of pulmonary arterial hypertension through relaxation of pulmonary arteries in lungs. 16 In addition, the acute effect of tadalafil as a reno protective agent was demonstrated in experimental renal ischemia/reperfusion injury model in the rat. 17 More recently, Wang et al demonstrated that tadalafil is effective and safe for the treatment of diabetic neuropathy as it increases regional blood flow in the sciatic nerve tissue and improves peripheral nerve function in type II diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies, the dose of tadalafil which achieved therapeutic effects varied from 0.5 to 10 mg/kg/day in different experimental works (Oh et al 2008;Ko et al, 2009;Sawamura et al, 2009). It was found that doses of 0.5 and 10 mg/kg tadalafil in rats simulate human doses of 2.5 and 40 mg/day, respectively (Sawamura et al, 2009).…”
Section: Experimental Designmentioning
confidence: 99%
“…It was found that doses of 0.5 and 10 mg/kg tadalafil in rats simulate human doses of 2.5 and 40 mg/day, respectively (Sawamura et al, 2009). Therefore, the doses of 1, 5 and 10 mg/kg per day of tadalafil were chosen in the study.…”
Section: Experimental Designmentioning
confidence: 99%
“…14,15) Four weeks after MCT treatment, systemic arterial pressure (SAP) and right ventricular systolic pressure (RVSP) were measured. Measurements of SAP and RVSP were initiated when stable pressures were recorded for more than 5 min.…”
Section: Cigarette Smoke Extract (Cse)+lps-induced Copd Model In Guinmentioning
confidence: 99%